Neurotrophins in carotid atherosclerosis and stenting. (31st December 2023) - Yaneva-Sirakova, Teodora; Traykov, Latchezar; Karamfiloff, Kiril; Petrov, Ivo; Hristova, Julieta; Vassilev, Dobrin
Abstract: Introduction: Carotid stenting is used with an expanding indications. The neurotrophins are a family of proteins that induce the survival, development, and function of neurons. Carotid stenting alters cerebral blood flow and can affect neurotrophins' levels. Material and methods: We included 78 people: 39 with significant carotid stenoses (CS) referred for carotid stenting (mean age 67.79 ± 10.53 years) and relatively healthy control group of 39 people without carotid and vertebral artery disease (mean age 57.42 ± 15.77 years). Brain derived reurotrophic factor (BDNF) and neuronal growth factor (NGF) concentrations were evaluated with ELISA method from venous blood – once for the control group; and for the carotid stenting group: before (n33), 24 h after (n22) and at least 1 month after (n18) carotid stenting. Results: There was a difference between the mean neurotrophins' concentration of patients with significant carotid stenoses and the group without: BDNF p  = 0.001, CI (-5.11 to −1.44) (3.10 ± 3.10 ng/ml in CS vs. 6.37 ± 4.67 ng/ml in controls); NGF p  = 0.049, CI (0.64–347.75), 195.67 ± 495.34 pg/ml in CS vs. 21.48 ± 52.81 pg/ml in controls. BDNF levels before carotid stenting (3.10 ± 3.10 ng/ml) were significantly lower than the postprocedural (4.99 ± 2.57 ng/ml) – p  < 0.0001, CI (-2.86 to −0.99). For NGF there was a tendency for lower values after stenting: 195.67 ± 495.34 pg/ml before vs. 94.92 ± 120.06 pg/ml after, but the result did not reach statistical significance. The neurotrophins levels one month after carotid stenting and controls' were not significantly different p  < 0.01 (BDNF 5.03 ± 4.75 ng/ml vs. 6.37 ± 4.67 ng/min; NGF 47.89 ± 54.68 pg/ml vs. 21.48 pg/ml). Discussion and conclusion: Periprocedural and mid-term concentrations of neurotrophins after carotid stenting change in non-linear model. This may be due to changes in cerebral perfusion and also might be involved in neuronal recovery and reparation after reperfusion. KEY MESSAGES: Periprocedural and mid-term concentrations of neurotrophins after carotid stenting change in non-linear model. As the majority of them are not specific, their periprocedural change can be used as a clinical correlate to guide changes or even success in carotid stenting. Changes in neutrophins' concentrations may be due to changes in cerebral perfusion and also might be involved in neuronal recovery and reparation after reperfusion. This goes in analogy with cardiac high-sensitive troponin, used as procedural guidance in coronary interventions.